Apathy is out selected poems = Ní ceadmhach neamhshuim : rogha dánta - Ó Ríordáin, Seán 1916-1977 (Bloodaxe Books, 2021)
"Seán Ó Ríordáin (1916-77) was the most important and most influential Irish-language poet of modern times. He revitalised poetry in Irish, combining the world of Irish literature with that of modern English and European literature, thus adding to the Irish tradition from the other side. His poems 'seek to answer fundamental questions about the nature of human existence and the place of the individual in a universe without meaning' (Gearóid Denvir). Many of Ó Ríordáin's poems came out of his struggle with the isolation, guilt and loneliness of life in mid-century Catholic Ireland experienced in Cork, the native locale also of the poet Greg Delanty, translator of Apathy Is Out. Ó Ríordáin's poems have been translated by many poets, but until now no single writer has translated the majority of the poems. This collection gives a much more unified sense of Ó Ríordáin's work, catching the poetry's verve, playfulness and range and also 'the music you still hear in Munster,/even in places where it has gone under'. It includes the dark, sorrowful poems Ó Ríordáin has usually represented with in anthologies but also poems of exuberance and celebration, notably 'Tulyar', one of the funniest satirical critiques of the Irish Church's attitude to sex which matches any similar attack by Patrick Kavanagh or Austin Clarke. Seán Ó Ríordáin renewed poetry in Irish by writing out of the modernist sense of alienation, fragmentation and identity, but he also saw beyond Modernism's confines to the connective matrix of our world.
Keywords: Ó Ríordáin, Seán -- 1916-1977; Lyrik; Ó Ríordáin, Seán / 1916-1977 / Translations into English; Poetry; Ó Ríordáin, Seán / 1916-1977; Translations; Anthologie